Healthy dietary patterns, foods, and risk of glioma: A systematic review and meta-analysis of observational studies - Shu, Long; Yu, Dan; Jin, Fubi (Frontiers in Nutrition, 2023)
Background: Accumulating epidemiological evidence has showed the favorable associations between healthy dietary patterns and risk of glioma, although the results remain inconclusive. Objective: We therefore carried out a systematic review and meta-analysis to summarize the evidence from previous published studies, and clarify the effect of healthy dietary patterns, typical healthy foods on glioma risk. Methods: PubMed, Web of Science, CNKI and Wan fang data were searched from inception until September 2022 for eligible studies. Two authors independently performed literature search, study selection, data extraction and quality assessment.Heterogeneity across studies was evaluated using the Cochran’s Q test and I2 statistic. According to heterogeneity, the fixed-effects model or random-effects model was selected to obtain the relative risk(RR) of the merger. Subgroup analysis, sensitivity analysis and publication bias were also used for our analyses. Results: Twenty-four articles reporting 28 studies with 7278 glioma cases and 2143528 participants, were included in our analysis. There was a reduced risk of glioma in the highest compared with the lowest category of healthy dietary patterns(RR=0.58; 95%CI:0.44-0.77; P<0.0001). Moreover, compared with the lowest intakes, the highest intakes of vegetables(RR=0.84; 95%CI: 0.73-0.96; P= 0.012) and fruits(RR=0.85; 95%CI: 0.72-1.00; P=0.045) significantly reduce the risk of glioma. The intakes of fresh fish, nuts, whole grains and dairy products showed no significant associations with the risk of glioma(P>0.05). Conclusions: Findings from this meta-analysis indicate that higher intakes of healthy dietary patterns, vegetables and fruits are significantly associated with the lower risk of glioma. Further studies, particularly prospective cohort studies, are required to confirm these findings.